Analysis of the c.1135G > A, c.1993A > G, c.2059T > C TAP2 gene variants and their relationship with latent tuberculosis infection in Mexico - Gerardo Cazarez-Navarro; Ivan Hernández-Cañaveral; Ana Gabriela Colima-Fausto; Jaime Palomares-Marín; Karel Licona-Lasteros; Ana Laura Pereira-Suarez; Sergio Yair Rodríguez-Preciado (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Tuberculosis (TB) is a worldwide public health problem with 10.6 million people falling ill and 1.5 million deaths every year. Latent tuberculosis infection (LTBI) is a condition in which an individual has been infected with Mycobacterium tuberculosis (Mtb) but does not show clinical signs and symptoms. The transporter associated with antigen processing (TAP2) protein plays a fundamental role in the immune response promoting the clearance of intracellular pathogens, such as Mtb. Our study aimed to determine the association between c.1135G > A (rs1800454), c.1993A > G (rs241447) and c.2059 T > C (rs241448) TAP2 gene variants with LTBI susceptibility. In this case-control study, 180 individuals (90 were LTBI-positive and 90 were controls) from shelters were analyzed. Genotyping of the polymorphisms was performed using the Applied Biosystems Step One Thermal Cycler Real-Time PCR allelic discrimination technology. The haplotypic analyses were performed with the Arlequin 3.5 software. The G allele (OR = 1.732, CI = 1.125–2.667, p = 0.012) and AG genotype of the c.1993A > G variant (p=<0.001) were associated with susceptibility to LTBI (p=<0.001), as well as the GAT, AAT, AAC, AGT haplotypes (p=<0.001). The c.1135G > A and c.2059 T > C variants were not associated with LTBI risk.